Improved function and strength in patients with knee osteoarthritis as a result of adding a two-day educational program to usual care. Prospective randomized trial - Rezende, M. U.; Brito, N. L.R.; Farias, F. E.S.; Silva, C. A.C.; Cernigoy, C. H.A.; Rodrigues da Silva, J. M. [UNESP]; Moreira, M. M.; Santana, O. F.N.; Hissadomi, M. I.; Frucchi, R.; Pasqualin, T.; Campos, G. C.; et al. (Elsevier, 2021)
Objective: The primary aim was to quantify the improvements on function and pain of patients with knee osteoarthritis (KOA), short education and low income by a two-day self-management program. Secondary aims were verifying if the program improves clinically relevant measures of weight and strength. Design: A prospective randomized clinical trial was conducted in a tertiary hospital in Brazil with 191 patients with Kellgren & Lawrence grades II and III KOA who were allocated to two groups: control (usual care- CG) and intervention (usual care and two days of an OA self-management program with a multiprofessional team - IG). Western Ontario and McMaster Universities Index (WOMAC), weight, body mass index (BMI), Timed up and go (TUG) and five Times Sit to Stand Test (FTSST) were assessed at baseline, six, 12 and 24 months. Results: Groups were similar at baseline (p ​> ​0.05). Both groups exhibited improved WOMAC total and subsets scores throughout the study (p ​< ​0.001). However, only IG improved WOMAC total and subsets in all follow-ups above 20% (minimally clinically important difference), with differences in WOMAC pain, function and total scores (p ​= ​0.001, p ​< ​0.001, and p ​< ​0.001, respectively) and best effect sizes at 1 year (0.355, 0.651 and 0.770, respectively). IG group lost weight (p ​< ​0.001) and BMI (p ​< ​0.01). Both groups exhibited improvements in TUG and FTSST (p ​< ​0.001) that remained in all evaluations. FTSST results favored the IG, p ​= ​0.032. Conclusions: An educational program to patients with KOA, short schooling and low income improves clinically important measures of pain and function.
Keywords: Clinical trial; Differential threshold; Education; Knee osteoarthritis; Minimal clinically important difference